Preclinical Pharmacokinetics and In Vitro Properties of GS-441524, a Potential Oral Drug Candidate for COVID-19 Treatment - Wang, Amy Q.; Hagen, Natalie R.; Padilha, Elias C.; Yang, Mengbi; Shah, Pranav; Chen, Catherine Z.; Huang, Wenwei; Terse, Pramod; Sanderson, Philip; Zheng, Wei; Xu, Xin (Frontiers in Pharmacology, 2022)
Preclinical pharmacokinetics (PK) and in vitro ADME properties of GS-441524, a potential oral agent for the treatment of Covid-19, were studied. GS-441524 was stable in vitro in liver microsomes, cytosols, and hepatocytes of mice, rats, monkeys, dogs, and humans. The plasma free fractions of GS-441524 were 62-78% across all studied species. The in vitro transporter study results showed that GS-441524 was a substrate of MDR1, BCRP, CNT3, ENT1, and ENT2; but not a substrate of CNT1, CNT2, and ENT4. GS-441524 had a low to moderate plasma clearance (CLp), ranging from 4.1 mL/min/kg in dogs to 26 mL/min/kg in mice; the steady state volume distribution (Vdss) ranged from 0.9 L/kg in dogs to 2.2 L/kg in mice after IV administration. Urinary excretion appeared to be the major elimination process for GS-441524. Following oral administration, the oral bioavailability was 8.3% in monkeys, 33% in rats, 39% in mice, and 85% in dogs. The PK and ADME properties of GS-441524 support its further development as an oral drug candidate.